Writing Poetry from the Fringes of Globalization - N. SUGBO, VICTOR (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Globalization has not only affected trade and politics of countries around the globe. It has also affected even the writing of poetry, more particularly the poet who aims to improve his craft. This paper examines the position of the Third World poet in relation to world poetry and the issues he confronts as he wrestles with his craft to produce new poetry. Being in a Third World country assumes that the poet is in a disadvantageous position, primarily because he is not in the center of political, economic, and cultural power. For this reason, he is assumed to have limited poetic resources -that would guide him in developing his craft. This, however, is not so at present since the Internet can keep him abreast with the latest developments in world poetry. With the abundance of knowledge and information on poetry available in the web, the poet faces a set of issues in writing his craft.